Interaction of sex and cannabis in adult in vivo brain imaging studies: A systematic review. (January 2022) - Francis, Ashley M.; Bissonnette, Jenna N.; MacNeil, Sarah E.; Crocker, Candice E.; Tibbo, Philip G.; Fisher, Derek J.
Cannabis has been shown to cause structural and functional neurocognitive changes in heavy users. Cannabis use initiation aligns with brain development trajectories; therefore, it is imperative that the potential neurological implications of cannabis use are understood. Males and females reach neurodevelopmental milestones at different rates making it necessary to consider biological sex in all cannabis and brain-based research. Through use of a systamatic review in accordance with PRISMA guidelines, we aimed to understand the interaction between biological sex and cannabis use on brain-based markers. In total, 18 articles containing a sex-based analysis of cannabis users were identified. While the majority of studies ( n  = 11) reported no sex by cannabis use interactions on brain-based markers, those that reported findings ( n  = 8) suggest females may be more susceptible to cannabis' neurotoxic effects. Unfortunately, a large portion of the literature was excluded due to no sex-based analysis. In addition, studies that reported no sex differences often contained a reduced number of females which may result in some studies being underpowered for sex-based analyses, making it difficult to draw firm conclusions. Suggestions to improve cannabis and sex-based reseach are proposed.